Prevalence of Ineffective Haplotypes at the Rice Blast Resistance (R) Gene Loci in Chinese Elite Hybrid Rice Varieties Revealed by Sequence-Based Molecular Diagnosis - Xiao, Gui; Yang, Jianyuan; Zhu, Xiaoyuan; Wu, Jun; Zhou, Bo (Springer, 2020)
Multiple haplotypes at the same rice blastR-gene locus share extremely high sequence similarity, which makes the gene diagnostic method using molecular markers less effective in differentiation from one another. The composition and distribution pattern of deployedRgenes/haplotypes in elite rice varieties has not been extensively analyzed. In this study, we employed PCR amplification and sequencing approach for the diagnosis ofR-gene haplotypes in 54 Chinese elite rice varieties. A varied number of functional and nonfunctional haplotypes of 4 target majorR-gene loci, i.e.,Pi2/9,Pi5,Pik, andPib, were deduced by referring to the reference sequences of knownRgenes. Functional haplotypes accounted for relatively low frequencies for thePi2/9(15%) andPik(9%) loci but for relatively high frequencies for thePi5(50%) andPib(54%) loci. Intriguingly, significant frequencies of 33%, 39%, 46% of non-functional haplotypes at thePi2/9,Pik, andPibloci, respectively, with traceable original donors were identified, suggesting that they were most likely unintentionally spread by using undesirable donors in various breeding programs. In the case ofPi5locus, only a single haplotype, i.e.,Pi5was identified. The reactions of 54 rice varieties to the differential isolates were evaluated, which showed a good correlation to the frequency of cognate avirulence (Avr) genes or haplotypes in the differential isolates. FourRgenes, i.e.,Pi2,Piz-t,Pi50, andPikmwere found to contribute significantly to the resistance of the elite rice varieties. Other two genes,Pi9andPikh, which were not utilized in rice varieties, showed promising values in breeding durable resistance due to their high resistance frequencies to the contemporary rice blast population. The sequence-based molecular diagnosis provided a promising approach for the identification and verification of haplotypes in differentR-gene loci and effectiveRgenes valuable for breeding durable rice resistance to rice blast.